LAPORAN KASUS: PSORIASIS VULGARIS YANG DITERAPI DENGAN LASER ULTRAVIOLET B EXCIMER - Pinkan Putri Nabila; Hans Utama; Tiar Marina Octyvani (Fakultas Kedokteran Universitas Trisakti, 2026)
A 40-year-old man with recurrent psoriasis vulgaris in the lumbosacral region and comorbid obesity. The patient had previously undergone systemic therapy with immunosuppressive drugs at another clinic; however, the psoriatic lesions recurred after treatment was discontinued. Dermatological examination revealed erythematous-hyperpigmented lesions sharply demarcated by a thick, silvery-white plaque. Phototherapy with a 308 nm excimer laser at a dose of 200 mJ/cm² or 1.3 MED—where the minimal erythema dose (MED) is 150 mJ/cm² was administered in three sessions with two-week intervals. Therapeutic efficacy was evaluated based on clinical examination results following the third procedure. There was a reduction in skin lesion thickness and infiltration compared to baseline parameters. This case demonstrates that 308 nm excimer laser therapy is an effective and relatively safe method for treating recurrent localized psoriasis vulgaris. Specifically, three treatment sessions resulted in clinical improvement of the condition.